Influence of pulse-delay curing on sorption and solubility of a composite resin - Lawrence Gonzaga Lopes; Alfeu da Veiga Jardim Filho; João Batista de Souza; Denilson Rabelo; Eduardo Batista Franco; Gersinei Carlos de Freitas (University of São Paulo, 2009)
The purpose of this study was to evaluate the sorption and solubility of a composite resin (TPH³; Dentsply) cured with halogen light due to different storage media and curing modes. The methodology was based on the ISO 4049 standard. Two independent groups were established according to the storage time (7 days-G1; 60 days-G2). A stainless steel mould (2 mm x 8 mm Ø) was used. The selected curing modes were: I (Conventional - C): 40s - 600 mW/cm²; II (Pulse I - PD): 3 s - 200 mW/cm² + 2 min (delay) + 39 s - 600 mW/cm²; III (Pulse II): 10 s - 200 mW/cm² + 2 min (delay) + 37 s - 600 mW/cm²; IV (Pulse III): 3 s- 600 mW/cm² + 2 min (delay) + 37 s -600 mW/cm². The media used were: distilled water, 75% ethanol and 100% chlorophorm. Five repetitions were made for each group. The specimens were placed in a desiccator at 37ºC for 24 h and, after that, at 23ºC for 1 h to be weighed until a constant mass (m1) was obtained. The discs were immersed separately into the 3 media for 7 days (G1) and 60 days (G2), and thereafter reweighed (m2). The reconditioning in the desiccator was done until a constant mass (m3) was obtained. Sorption and solubility were calculated and the data of G1 and the sorption data of G2 were subjected to two-way ANOVA and Tukey's tests (p=0.05). The solubility data of G2 were analyzed by Kruskal-Wallis test (p=0.05). For G1 and G2, no statistically significant differences were found in sorption among curing techniques (p>0.05). The solubility values were negative, which means that there was mass gain. Regarding the storage media, in G2 chlorophorm had the highest sorption values. It may be concluded that the curing modes (C and PD I, II and III) did not affect the sorption of the tested composite resin. However, different storage media influenced sorption behavior. The solubility test demonstrated negative data, masking the real solubility.